2014
DOI: 10.3109/14767058.2014.963046
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with higher oxytocin requirements in labor

Abstract: Objective To identify clinical characteristics associated with high maximum oxytocin doses in women who achieve complete cervical dilation. Methods A retrospective nested case-control study was performed within a cohort of all term women at a single center between 2004-2008 who reached the second stage of labor. Cases were defined as women who had a maximum oxytocin dose during labor >20 mu/min, while women in the control group had a maximum oxytocin dose during labor of ≤20 mu/min. Exclusion criteria includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
6
16
0
1
Order By: Relevance
“…In low-dose regimens, women received 5.74 µg and while women in high-dose regimens received 7.98 µg [37], higher than the total amount found in our study. Similar to our ndings, Frey et al (2015) found that induction was associated with higher maximum oxytocin doses [38]. The fact that higher amounts of oxytocin were administrated to women following induction of labour is understandable, given that the infusion is likely to be continued for a more extended period.…”
Section: Discussionsupporting
confidence: 84%
“…In low-dose regimens, women received 5.74 µg and while women in high-dose regimens received 7.98 µg [37], higher than the total amount found in our study. Similar to our ndings, Frey et al (2015) found that induction was associated with higher maximum oxytocin doses [38]. The fact that higher amounts of oxytocin were administrated to women following induction of labour is understandable, given that the infusion is likely to be continued for a more extended period.…”
Section: Discussionsupporting
confidence: 84%
“…This study corroborated the findings by Frey et al demonstrating that maternal body mass index (BMI), maternal diabetes, and labor induction were risk factors for requiring high doses of oxytocin to achieve delivery 6 . We found that HDR patients were more likely than LDR patients to have cesarean sections for first stage arrest and less likely to have cesarean sections for non-reassuring fetal status.…”
Section: Commentsupporting
confidence: 90%
“…These groups were selected because they fell below the 25 th percentile and above the 95 th percentile of oxytocin dose within our population of laboring patients 6 . Our institutional protocol for oxytocin administration allows for either high-dose or low-dose regimens at the discretion of the obstetric provider.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The resultant need for a higher oxytocin dose to cause adequate uterine contraction in vivo has also been shown in labouring women who received oxytocin for labour augmentation. 15 Furthermore, there are studies suggesting that use of MgSO 4 may lead to increased requirements for oxytocin 16,17 or that MgSO 4 may increase PPH in preeclamptic patients. 17 Nevertheless, further studies are warranted to assess these potential interactions.…”
Section: Résumémentioning
confidence: 99%